Analysis of stock market instruments for novice investor - Sadykova, S. T. (Journal of Economic Research & Business Administration, 2015)
This article presents the vision of the novice investor in the market of urgent financial instruments. Analysis of derivatives for Kazakhstan stock exchange KASE is presented at theoretical level. The positive and negative aspects of the stock market , futures and options contracts are identified.Financial risks can be linked with for example sales of products, the depreciation of capital invested in assets, purchase of assets , etc.For this purpose, the derivative financial instruments (futures contracts , derivatives ) were invented and an operation to reduce risk with these derivatives is called hedging.